Uncovering a Genetic Polymorphism Located in Huntingtin Associated Protein 1 in Modulation of Central Pain Sensitization Signaling Pathways - Gloor, Yvonne; Matthey, Alain; Sobo, Komla; Mouterde, Médéric; Kosek, Eva; Pickering, Gisèle; Poloni, Estella S.; Cedraschi, Christine; Ehret, Georg; Desmeules, Jules A. (Frontiers in Neuroscience, 2022)
Fibromyalgia syndrome (FMS) is characterized by widespread pain and increased sensitivity to nociceptive stimulus or tenderness. While familial aggregation could suggest a potential hereditary component in FMS development, isolation of genetic determinants has proven difficult due to the multi-factorial nature and complexity of the syndrome. Central sensitization is thought to be one of the key mechanisms leading to FMS in a subset of patients. Enhanced central pain signaling can be measured using the Nociceptive Flexion Reflex (NFR) or RIII threshold. We performed a genome-wide association study (GWAS) using an array to genotype 258’756 human genetic polymorphisms in 225 FMS patients and 77 healthy volunteers and searched for genetic variants associated with a lowered NFR threshold. We have identified a potential association between a single nucleotide polymorphism resulting in a common non-synonymous coding mutation in the HAP1 gene (rs4796604, MAF = 0.5) and the NFR threshold (p = 4.78E-06). The Hap1 protein is involved in trafficking and is particularly enriched in neurons. Our results suggest a possible involvement of the neuronal trafficking protein HAP1 in modulating pain signaling pathways and thus participate in the establishment of the NFR threshold.